Nitric Oxide Mediates Inflammation in Type II Diabetes Mellitus through the PPARγ/eNOS Signaling Pathway - Hua Guo; Qinglan Zhang; Haipo Yuan; Lin Zhou; Fang-fang Li; Sheng-Ming Wang; Gang Shi; Maojuan Wang (PPAR Research)
Inflammation accounts for the process of type II diabetes mellitus (T2DM), the specific mechanism of which is still to be elucidated yet. Nitric oxide (NO), a critical inflammation regulator, the role of which is the inflammation of T2DM, is rarely reported. Therefore, our study is aimed at exploring the effect of NO on the inflammation in T2DM and the corresponding mechanism. We analyzed the NO levels in plasma samples from T2DM patients and paired healthy adults by Nitric Oxide Analyzer then measured the expression of inflammatory cytokines (C-reactive protein, heptoglobin, IL-1β, TNF-α, IL-6) in insulin-induced HepG2 cells treated with NO donor or NO scavenger, and the PPARγ, eNOS, C-reactive protein, heptoglobin, IL-1β, TNF-α, and IL-6 levels were detected by RT-PCR and western blot in insulin-induced HepG2 cells transfected with si-PPARγ. The results showed that excess NO increased the inflammation marker levels in T2DM, which is activated by the PPARγ/eNOS pathway. These findings will strengthen the understanding of NO in T2DM and provide a new target for the treatment of T2DM.